2019
DOI: 10.2478/pomr-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Analysis of Causes of Washout of Gdynia-Orłowo Sea-Shore During the Flood in the Kacza River Estuary

Abstract: In July 2016 in the Three-city agglomeration a rainfall episode of over a day duration and 150 mm summary rainfall height, occurred. This situation, extreme as for Polish conditions, caused significant freshets in rivers and streams running into Gdansk Bay, the Baltic Sea, and serving as collectors of rainfall waters for the sea-coast towns. In many areas of the Three-city flood phenomena and overflows took place. The flood also occurred in the catchment area of the Kacza river in Gdynia. The passing of flood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Another cause of this risk is also the changing characteristics of precipitation as a result of global climate change [47,63]. Such floods are dangerous to people and destroy the urban infrastructure due to the overflow of the stormwater drainage system [75] and increase erosion of the land surface [76]. Generally, urban development will not only boost peak discharge but will also elevate the runoff volume and the extent of the flooded zone within a catchment.…”
Section: Discussionmentioning
confidence: 99%
“…Another cause of this risk is also the changing characteristics of precipitation as a result of global climate change [47,63]. Such floods are dangerous to people and destroy the urban infrastructure due to the overflow of the stormwater drainage system [75] and increase erosion of the land surface [76]. Generally, urban development will not only boost peak discharge but will also elevate the runoff volume and the extent of the flooded zone within a catchment.…”
Section: Discussionmentioning
confidence: 99%
“…In version 5.0, two-dimensional modeling of flow, as well as sediment transport modeling capabilities were introduced. In the literature, many studies have focused on utilizing HEC-RAS 2-D to generate flood inundation maps in urban areas (Abdelkarim et al, 2019;David & Schmalz, 2020;Haltas, Tayfur & Elci, 2016;Marko et al, 2018;Rangari, Umamahesh & Bhatt, 2019;Sharif et al, 2016;Surwase & Manjusree, 2019;Syafri, Hadi & Suprayogi, 2020;Szydłowski, 2019;Yalcin, 2020). Quirogaa et al (2016) indicated the good performance of the inundation extent simulated by HEC-RAS 2-D when compared to that detected by a satellite image for the flood event February 2014 in the Bolivian Amazonia.…”
Section: Introductionmentioning
confidence: 99%
“…Ücretsiz olarak servis edilmiş olması, pratik yapısından ve hızlı çözüm alabilme kapasitesinden dolayı uygulama alanlarında oldukça yoğun kullanıma sahip olan HEC-RAS yazılımı da bu özel yazılımlardan biridir. Uygulama çalışmalarındaki yoğun kullanımının yanında literatürde, akademik alanda da HEC-RAS yazılımı kullanılarak yapılan; akarsu üzerinde bulunan çoklu köprü sistemlerinin akış alanı üzerindeki etkilerinin 1 boyutlu ve 2 boyutlu olarak çözümlendiği ve sonuçların karşılaştırıldığı çalışmalar [3], Taşkın sırasında akarsuyun denize döküldüğü kıyı hattında oluşan oyulmaların ve zararların modellendiği çalışmalar [4], akarsuyun manning pürüzlülük katsayısının kalibrasyonunun yapılması için taşkın sırasında kaydedilen istasyon ölçümleri ile HEC-RAS programından alınan model sonuçlarının karşılaştırıldığı çalışmalar [5,6], baraj yıkılması durumunda mansapta oluşacak taşkın yayılım alanlarının haritasının 2 boyutlu modellemesi hakkında çalışmalar [7], deniz su seviyesinin taşkın alanlarına etkilerinin sayısal modeller kullanılarak incelendiği çalışmalar [8] ve taşkın risk haritasını hazırlamak veya daha detaylı hale getirmek için sayısal modellerin kullanıldığı [9] çalışmalar, akarsuda taşkın modellemesinin yapıldığı çalışmalar [10] gibi akışkan hareketi üzerine çeşitli çalışmalar mevcuttur.…”
Section: Introductionunclassified